Texture staling of pound cakes assessed by front face fluorescence spectroscopy in tandem with chemometric analysis. Issue 6 (28th June 2022) - Nhouchi, Zeineb; Karoui, Romdhane
Abstract: Two vegetal oils have been selected for the formulation of pound cakes, rapeseed oil (RO) and palm oil (PO). The freshness of these products has been monitored during 58 days of storage. The RO pound cakes of 58 days as well as PO pound cakes presented higher values ( p  < .05) of hardness (N), Young's modulus (N.cm −2 ) and compressive stress (N.cm −2 ) than those aged of 5 days. For both vitamin A and tryptophan spectra, the maximum of fluorescence intensity varied according to the aging period. For both RO and PO recipes, lipid oxidation indicators (peroxide value, para‐anisidine value, and total oxidation value [TOTOX]) were interestingly correlated to Young's modulus ( R 2  = 0.99) as well as compressive stress ( R 2  = 0.99), using polynomial model. The application of partial least squares regression to the vitamin A spectra provided excellent predictive results for both compressive stress ( R 2  = 0.99) and TOTOX ( R 2  = 0.99). Good results were observed for tryptophan spectra for the prediction of TOTOX ( R 2  = 0.77). Thus, the use of front face fluorescence spectroscopy may provide rapid and accurate results for the monitoring of pound cakes freshness throughout storage.